PENGEMBANGAN MEDIA BOOKLET DIGITAL BERBANTUAN APLIKASI CANVA PADA PELAJARAN IPAS KELAS IV SD NEGERI KAMPUNG BAROH - Anisa Nadia; Sukirno; Juliati (STKIP Subang, 2026)
The study activities of Natural and Social Sciences (IPAS) in several elementary schools still face some challenges related to the limited learning media used, resulting in students' understanding of the material not being optimal. Based on this situation, there is a need to develop more innovative, engaging, easy-to-use media that aligns with the characteristics of elementary school students. The aim of this research is to design and develop a digital Booklet media by utilizing the Canva application as a supportive tool for IPAS learning for fourth-grade students at SD Negeri Kampung Baroh, as well as to determine its feasibility, practicality, and effectiveness in improving students' learning outcomes. The research method used is Research and Development (R&D) with the ADDIE model, which consists of the stages of analysis, design, development, implementation, and evaluation. The research results showed that content expert validation received a score of 100% (highly suitable), media expert 92% (highly suitable), and language expert 94% (highly suitable). The practicality test showed that teachers scored 100% and students 90.74% (very practical). The effectiveness test, through a comparison of pretest and posttest, showed an average N-gain score of 0.74, categorized as high. Thus, the digital Booklet assisted by the Canva application is declared feasible, practical, and effective to implement in IPAS learning. Based on these research results, it is suggested that the digital Booklet assisted by the Canva application can be utilized more widely in the learning process, not limited to IPAS learning, but also developed for other subjects at the elementary school level.